Ahkam al-Laqit: K onsep Islam dalam Menangani Anak Jalanan di Indonesia - Rifanto Bin Ridwan; Ibnor Azli Ibrahim (TSAQAFAH, 2012)
Although the concept of al-laqitis considered not suitable to the conditions of street children in Indonesia, but in fact, both have the same root of causes. Meanwhile, the presence of street children in Indonesia cause many complex social problems. With the increasing number of street children filling the corners of the city ,it will further increase and cause the social problems. According to national data released by Indonesian National Social Welfare Board,that the increase in street children before the economic crisis hit the country Indonesia for 15%,and this figure increased to 100% in the period of crisis. This article will review the existence of this group and look at the rights and obligations of the state in handling them according to Islamic perspective. Beside of the library study ,in order to get the viewpoint of Islam this paper conducts comparative field study which attempts to look closely at the reality of this group in more concrete condition. In the end, this paper finds a weakness in the system of state management in political, social and economic aspects which in fact become the major factor of the emergence of marginalized groups which form a community that bring social problem.Finally ,this paper highlights the role of Islam in dealing with this issue of street children. The history recorded that Islam was at the forefront of combating the presence of abandoned children. These all in Islam is a form of social awareness and takaful ijtima’i.